Improved base editor for efficient editing in GC contexts in rabbits with an optimized AID‐Cas9 fusion. Issue 8 (9th May 2019) - Liu, Zhiquan; Shan, Huanhuan; Chen, Siyu; Chen, Mao; Zhang, Quanjun; Lai, Liangxue; Li, Zhanjun
ABSTRACT: Cytidine base editors, which are composed of a cytidine deaminase fused to clustered regularly interspaced short palindromic repeat (CRISPR)–associated protein 9 (Cas9) nickase, enable the efficient conversion of the C·G base pair to T·A in various organisms. However, the currently used rat apolipoprotein B mRNA‐editing enzyme, catalytic polypeptide 1(rA1)–based BE3 is often inefficient in target Cs that are immediately downstream of a G (GC context). Here, we observed that, with an 11‐nt editing window, an optimized activation‐induced cytidine deaminase (AID)‐Cas9 fusion can efficiently convert C to T in a variety of sequence contexts in rabbits. Strikingly, the enhanced AID‐Cas9 fusion (eAID‐BE4max) has significant effectiveness of inducing Tyr p.R299H mutation in GC contexts (from 16.67 to 83.33%) in comparison with BE3 in founder rabbits. Furthermore, the engineered AID‐Cas9 variants were produced with reduced bystander activity [eAID (N51G)‐BE4max] and increased genome‐targeting scope (eAID‐NG‐BE4max). Overall, this work provides a series of improved tools that were generated using optimized AID‐Cas9 fusions and associated engineered variants that can be used for efficient and versatile C‐to‐T base editing, especially in GC contexts.—Liu, Z., Shan, H., Chen, S., Chen, M., Zhang, Q., Lai, L., Li, Z. Improved base editor for efficient editing in GC contexts in rabbits with an optimized AID‐Cas9 fusion. FASEB J. 33, 9210–9219 (2019). www.fasebj.org